When is the Critical Time for Soft Tissue Reconstruction of Open Tibia Fracture Patients? - Lee, Seung Yeol; Seong, Ik Hyun; Park, Bo Young (Journal of Reconstructive Microsurgery, 2020)
Background The timing of soft tissue reconstruction for soft-tissue defect in patients with open fractures in the lower extremity is known to be critical for successful outcomes. However, medical advances, including development of dressing materials and refinement in the microsurgical techniques, might have undergone modifications in this “critical period.” There have been no studies on the role of timing on reconstructive outcomes. Thus, we have analyzed the effect of reconstruction timing on optimal surgical outcomes and complication rates in a single type of lower extremity injury.Methods Data of patients who underwent microvascular free tissue transfer with an open fracture in the lower extremity from 2014 through 2016 were retrospectively reviewed (n = 103). Surgical outcomes, including flap complication rate, flap revision rate, and long-term bony complications, were analyzed serially in accordance with time interval until coverage using the receiver operating characteristic (ROC) curve analysis. Significant factors with a p < 0.05 in the univariate analysis were included in the multivariate logistic regression model to identify independent risk factors.Results A total of 46 patients (33 males and 13 females) were finally included in the study. Based on the association between surgical timing and flap-related complication rate, the best cutoff period for surgery was 33 days, with an area under the curve of 0.658 (p = 0.040). Further, in the revision rate, the cutoff period was identified as 10 days (p = 0.016). Regarding the incidence of bony complications, ROC curve showed that the maximal period until operation was 91 days with no influence on the occurrence of bony complications (p = 0.029).Conclusion Although the best method is an early reconstruction, many modalities such as negative pressure wound therapy play a role as a temporary measure. Our study suggests that the acute or early period for successful reconstruction might be extended compared with previous studies.
Keywords: reconstruction timing; free flap reconstruction; open fracture